First update of the International Xenotransplantation Association consensus statement on conditions for undertaking clinical trials of porcine islet products in type 1 diabetes—Chapter 5: recipient monitoring and response plan for preventing disease transmission. (26th February 2016) - Denner, Joachim; Tönjes, Ralf R.; Takeuchi, Yasu; Fishman, Jay; Scobie, Linda
Abstract: Xenotransplantation of porcine cells, tissues, and organs may be associated with the transmission of porcine microorganisms to the human recipient. A previous, 2009, version of this consensus statement focused on strategies to prevent transmission of porcine endogenous retroviruses (PERVs). This version addresses potential transmission of all porcine microorganisms including monitoring of the recipient and provides suggested approaches to the monitoring and prevention of disease transmission. Prior analyses assumed that most microorganisms other than the endogenous retroviruses could be eliminated from donor animals under appropriate conditions which have been called "designated pathogen‐free" (DPF) source animal production. PERVs integrated as proviruses in the genome of all pigs cannot be eliminated in that manner and represent a unique risk. Certain microorganisms are by nature difficult to eliminate even under DPF conditions; any such clinically relevant microorganisms should be included in pig screening programs. With the use of porcine islets in clinical trials, special consideration has to be given to the presence of microorganisms in the isolated islet tissue to be used and also to the potential use of encapsulation. It is proposed that microorganisms absent in the donor animals by sensitive microbiological examination do not need to be monitored in the transplant recipient; this will reduce costs and screening requirements. Valid detection assays for donor and manufacturing‐derived microorganisms must be established. Special consideration is needed to preempt potential unknown pathogens which may pose a risk to the recipient. This statement summarizes the main achievements in the field since 2009 and focus on issues and solutions with microorganisms other than PERV.